A Comparative Analysis of Indonesia’s Copper Export Competitiveness to China - Putri Fadia Azzahra; Muhammad Husaini (Cita konsultindo, 2024)
Copper is a commodity widely used in various industries; therefore, the copper export value and the demand for copper have continued to increase in the past few decades. Indonesia is the 10th country with the highest copper reserves globally, but its export value is still lower than many countries. The study aims to analyze the comparative competitiveness between copper exports from Indonesia, Malaysia, Thailand, and the Philippines to China during 2018 - 2022. The methods used include the Trade Specialization Index (TSI), Revealed Comparative Advantage (RCA), and Export Competitiveness Index (ECI). The results showed that on average in 2018 - 2022, Indonesia is an exporting country with no comparative advantage but has an increasing trend of competitiveness in China. Meanwhile, Malaysia and the Philippines are exporting countries with a comparative advantage and an increasing trend of competitiveness in China.Thailand is an importing country with no comparative advantage but has an increasing trend of competitiveness in China.